Diseño e implementación de un ascensor de carga de capacidad de una tonelada para la empresa Cerrejón en faenas mineras (2021)
In this project, the design and subsequent construction of a freight elevator essential for the maintenance operations of the Cerrejón Company was carried out, this allowed for analysis of the selection of materials, calculations and required details. The elevator has a capacity of 1000 Kg, with an electric traction system for lifting a transport basket that allows the correct vertical movement of tools, spare parts and parts for truck maintenance